Do the Headlines of Croatian Scientific Publications Catch One's Eye? - Nikolić, Davor; Grgić, Ana (2014)
In the western tradition the scientific manner of thinking (which starts with the rationalism of the Modern Age) was generally considered opposed to the rhetorical discourse. Since the 1970s these two opposed poles have become complementary in many ways because it has been noticed that the language of scientific discourse is deeply figurative. In contemporary understanding of metaphors as the results of cognitive processes (and not simply linguistic ornament) the metaphors are considered as a necessary element of every discourse, even the scientific one. The same can be applied to the other figures and tropes. Contemporary rhetorical analyses of scientific discourse have mainly focused on just one text or more texts belonging to the same author, same subject, and same time, i.e. to the same context (for instance the works of Ch. Darwin, A. Einstein or M. Planck). It is interesting to observe that for the most part these analyses used texts belonging to the area of natural sciences (science in its narrow and even primary meaning for English speakers). This was in accordance with the belief of non-figurative, i.e. extremely rational nature of such texts. Relatively small attention was given to the figures in the headlines of scientific publications which is very strange if we know the importance of headlines in non-scientific genres, for instance in newspaper headlines. One of the important functions of any headline (in any discourse) is to attract the potential reader's attention. The differences between scientific genres should be visible in the structure of the publication headlines. It is expected that independent publications (books and proceedings) use figuratively shaped headlines more frequently because they need to attract the potential readers and buyers – the headline therefore has a marketing role. The headlines of talks at the scientific meetings also probably tend to use figures of speech in order to attract potential listeners (because the scientific talks are basically unique). After the talk transforms to a written paper (for publishing in the conference proceedings or a journal) there is a possibility that the headline will become less figurative. The aim of this research is to determine the figurativeness of the headlines of Croatian scientific publications in the basic scientific areas. The object of the analysis are the book headlines, journal paper headlines, conference talk headlines and the full papers in the conference proceedings. Besides making the list of figurative headlines, the aim is to analyze employed figures, to determine their frequency and to demonstrate their function and the argumentation value. Specific attention was given to the authors which used figurative headlines for multiple papers.
Projekt MZOS
ENG